2011
DOI: 10.1007/s00415-011-5926-z
|View full text |Cite
|
Sign up to set email alerts
|

Do supine position and deprivation of visual environment influence spatial neglect?

Abstract: It has been suggested that in spatial neglect, placing the patient in a supine position and performing tasks in the dark would reduce the rightward bias in line bisection and cancellation tasks. However, these findings remain debated and have not been extended to other tasks such as reading or visual exploration. Here, in the same study, we examined the effect of body position (BP) and visual environment (VE) on relatively ecological tests of spatial neglect. Among 17 patients with right-hemisphere stroke, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The two experiments showed that participants made generally more bisection errors when they could see their hands and the workspace as compared to the conditions where they only saw the stimuli and the cursor. This finding falls into line with the observation that reducing surrounding visual information can improve visuo-spatial performance in spatial neglect (Chokron, Colliot, & Bartolomeo, 2004;Gassama, Deplancke, Saj, Honore, & Rousseaux, 2011;Hjaltason & Tegner, 1992). This could be due to the fact that attention is less captured by visual distractors.…”
Section: Discussionsupporting
confidence: 88%
“…The two experiments showed that participants made generally more bisection errors when they could see their hands and the workspace as compared to the conditions where they only saw the stimuli and the cursor. This finding falls into line with the observation that reducing surrounding visual information can improve visuo-spatial performance in spatial neglect (Chokron, Colliot, & Bartolomeo, 2004;Gassama, Deplancke, Saj, Honore, & Rousseaux, 2011;Hjaltason & Tegner, 1992). This could be due to the fact that attention is less captured by visual distractors.…”
Section: Discussionsupporting
confidence: 88%
“…This was done in order to quantify patients' baseline as well as short- and long-term changes in visuospatial biases. Neglect severity was measured with the Schenkenberg line bisection task [36] (18 horizontal lines, 10–20 cm) and a variant of the bell cancellation test [37] (with 35 animal targets (among distractor objects)) [38]. Four equivalent animal search displays were used, each divided into seven virtual columns (each containing 5 targets).…”
Section: Methodsmentioning
confidence: 99%
“…Since the majority of studies did not report spatial biases separately for male and female participants, we also calculated the percentage of male participants in each study where this data was available. Nineteen studies did not report the sex of their participants and the data from the following studies were therefore not included in this analysis: (Andrews et al 2017;Barton et al 1998;Binetti et al 2011;Corazzini et al 2005;Daini et al 2008;Doricchi et al 2002;Gassama et al 2011;Grossi et al 1999;Hatin et al 2012;Luauté et al 2012;Mennemeier et al 1997Mennemeier et al , 2001Plummer et al 2006;Richard et al 2004;Striemer and Danckert 2010;Vallar et al 2000;Veronelli et al 2014b;Williamson et al 2018;Zeller and Hullin 2018).…”
Section: Moderatorsmentioning
confidence: 99%